The Politics of Emotion and Kinship Power: The Analysis of Empress Dowager Lü and the Crisis of Legitimacy in the Early Han Dynasty - Thaminlad, Apinun (ARU Research Journal Humanities and Social Sciences, 2026)
This academic article examines the political role of Empress Dowager Lü during the early Han dynasty by applying the frameworks of the politics of emotion and kinship politics to an interpretation of the Shiji and relevant scholarship. It challenges conventional historiography, which has often portrayed her solely as a ruthless female ruler, and instead considers the relationship among her attachment to her son, fear of losing political status, competition over imperial succession, and the constraints imposed on women within a patriarchal political structure. The synthesis and interpretation indicate that her use of violence and delegation of power to members of the Lü clan cannot be explained solely by personal emotion. Rather, these actions resulted from the interaction among personal motivations, political instability, and the power structure of the imperial court. Although such measures temporarily strengthened the political position of Empress Dowager Lü and her clan, they simultaneously intensified conflict with the Liu imperial house and established court officials, thereby undermining the legitimacy and long-term sustainability of Lü clan power. The article therefore proposes understanding Empress Dowager Lü as a political actor whose decisions were shaped by the interaction between personal motivations and structural conditions. This perspective offers a more nuanced understanding of the roles of women, emotion, and kinship in ancient Chinese politics.